Covalently crosslinked sodium alginate/poly(sodium p-styrenesulfonate) cryogels for selective removal of methylene blue. (1st February 2023) - Yin, Tianyu; Zhang, Xinyu; Shao, Shuai; Xiang, Tao; Zhou, Shaobing
Abstract: Adsorbents with high adsorption capacity, sustainability, and reusability are desired in wastewater treatments. Herein, covalently crosslinked microporous cryogels with efficient removal of cationic dyes are fabricated by freezing radical copolymerization using methacrylated alginate (AlgMA) and sodium p-styrenesulfonate (NaSS). The chemical structure, morphology, and thermal stability of the AlgMA/PNaSS cryogels are characterized. Compared with the AlgMA/PNaSS hydrogels with the same chemical composition fabricated by thermal-initiated polymerization, the cryogels show higher adsorption of methylene blue. The AlgMA/PNaSS (with a mass ratio of 1:2) possesses the maximum adsorption capacity for MB with 2300 mg/g under alkaline condition. In addition, the adsorption process of AlgMA/PNaSS cryogels fits the pseudo-second order model and Freundlich model, respectively. The AlgMA/PNaSS cryogels also reveal selective adsorption capacity and reusability after regeneration, which own unchanged corrected adsorption capacity during five adsorption-desorption cycles. The AlgMA/PNaSS cryogels show great potential for use in wastewater treatments and intelligent separation. Graphical abstract: Unlabelled Image